Thinking styles and vocational identity among senior-year students in elite universities in mainland China. (September 2022) - Zhang, Li-fang; Li, Mengting; Fan, Weiqiao; Chang, Biru; Postiglione, Gerard A.
Highlights: Vocational identity status assessment is reliable and valid among Chinese university students. Creativity-generating thinking styles benefited career exploration and commitment. Norm-favoring thinking styles contributed to career self-doubt. Abstract: This research pioneered the investigation of the statistically predictive power of university students' thinking styles for their vocational identity – beyond age, sex, academic discipline, socioeconomic status, hometown locations, and institutional ranking. One thousand and seventy-two senior-year undergraduates randomly selected from nine elite universities in Shanghai, mainland China, responded to the six-scale version of the Thinking Styles Inventory – Revised II and the Vocational Identity Status Assessment (VISA) . Results showed that in-breadth (i.e., diverse) career exploration, in-depth (i.e., specific) career exploration, commitment making, commitment identification, and to some extent, career flexibility, called for both creativity-generating thinking styles and norm-favoring styles, particularly the former. Furthermore, creativity-generating styles went against career self-doubt, whereas norm-favoring thinking styles contributed to career self-doubt. The results also suggested that with the exception of two items, the newly translated Chinese version of the VISA is reliable and valid for assessing the vocational identity of senior-year Chinese university students. These findings have brought new insights into the literature on thinking styles and that on vocational identity. Meanwhile, the findings have practical implications for university students, academics, and career guidance counsellors.